2022
DOI: 10.1177/10731911221075761
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the German Five-Factor Narcissism Inventory and Construction of a Brief Form Using Ant Colony Optimization

Abstract: Narcissism is a multifaceted construct commonly conceptualized as comprising grandiose and vulnerable aspects in a two-factor model. While the manifold correlates of these aspects imposed a challenge for research on the structure of narcissism, recent models converge in a three-factor structure of agentic-extraverted, antagonistic, and neurotic aspects, capturing variance in different conceptualizations and correlates of narcissism. We construct and validate a German adaptation of the Five-Factor Narcissism In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 130 publications
4
36
1
Order By: Relevance
“…To have comparable scores across studies, we used regression‐based estimation of FFNI‐LF scores for studies using the FFNI‐SF (see Supporting Information), which is why we cannot report internal consistencies here. Studies used either the original English version, a German version (manuscript in prep., for material, see Jauk et al., 2021), or a Polish version (Rogoza et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…To have comparable scores across studies, we used regression‐based estimation of FFNI‐LF scores for studies using the FFNI‐SF (see Supporting Information), which is why we cannot report internal consistencies here. Studies used either the original English version, a German version (manuscript in prep., for material, see Jauk et al., 2021), or a Polish version (Rogoza et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In the first part of the study, participants answered a series of personality questionnaires presented in the order below. These include the Mini-IPIP6 (24 items, Sibley et al, 2011) measuring 6 personality traits, the SIAS-6 and the SPS-6 (6 items each, Peters et al, 2012) assessing social anxiety levels, 5 items we devised pertaining to expectations about AI-generated image technology ("I think current Artificial Intelligence algorithms can generate very realistic images"), of which we mixed with 5 items from the general attitudes towards AI scale to lower the former's saliency and the ATTRACTIVENESS AND REALITY 9 possibility of it priming the subjects about the task, (GAAIS, Schepman & Rodway, 2020) the FFNI-BF (30 items, Jauk et al, 2022) measuring 9 facets of narcissism; the R-GPTS (18 items, Freeman et al, 2021) measuring 2 dimensions related to paranoid thinking; and the IUS-12 (12 items, Carleton et al, 2007) measuring intolerance to uncertainty.…”
Section: Methodsmentioning
confidence: 99%
“…Since exploratory factor analyses of the FFNI subscales (Miller et al, 2016) and items (Rogoza et al, 2021) yielded a three-factor structure which appeared consistent with the TriMN, a growing body of research has been applying the FFNI(-SF) to capture agentic extraversion, narcissistic antagonism, and neuroticism. The factor analytic results were sometimes ambiguous (Rogoza et al, 2021), however, and attempts at modeling a simple structure for the FFNI using confirmatory factor analytic approaches provided unsatisfactory results (see Jauk et al, 2023).…”
Section: Operationalizations Of the Trimnmentioning
confidence: 99%
“…The aim of our first study was to assess and compare the respective factor structure of the FFNI-BF and a combination of NARQ and HSNS items as two potentially alternative operationalizations of the TriMN. With respect to the FFNI-BF, prior constrained measurement model analyses (i.e., confirmatory factor analyses [CFA]) indicated relatively poor fit for the simple structure model with three correlated factors (comparative fit index [CFI] = .65; root-mean-square error of approximation [RMSEA] = .09; Jauk et al, 2023). Using exploratory structural equation modeling, Jauk et al (2023) identified a properly fitting measurement model for the FFNI-BF (CFI = .97; RMSEA = .04), which, however, did not follow a simple structure as it included numerous cross-loadings and yielded distorted parameter estimates due to probable overfitting.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation